Dynamic power dissipation formulation for application in dynamic programming buffer insertion algorithm - Uttraphan, C. (Penerbit UTM Press, 2016)
Buffer insertion is a very effective technique to reduce propagation delay in nano-metre VLSI interconnects. There are two techniques for buffer insertion which are: (1) closed-form solution and (2) dynamic programming. Buffer insertion algorithm using dynamic programming is more useful than the closed-form solution as it allows the use of multiple buffer types and it can be used in tree structured interconnects. As design dimension shrinks, more buffers are needed to improve timing performance. However, the buffer itself consumes power and it has been shown that power dissipation of buffers is significant. Although there are many buffer insertion algorithms that were able to optimize propagation delay with power constraint, most of them used the closed-form solution. Hence, in this paper, we present a formulation to compute dynamic power dissipation of buffers for application in dynamic programming buffer insertion algorithm. The proposed formulation allows dynamic power dissipation of buffers to be computed incrementally. The technique is validated by comparing the formulation with the standard closed-form dynamic power equation. The advantage of the proposed formulation is demonstrated through a series of experiments where it is applied in van Ginneken’s algorithm. The results show that the output of the proposed formulation is consistent with the standard closed-form formulation. Furthermore, it also suggests that the proposed formulation is able to compute dynamic power dissipation for buffer insertion algorithm with multiple buffer types.